Educational articleSalvage brachytherapy in combination with interstitial hyperthermia for locally recurrent prostate carcinoma following external beam radiation therapy: a prospective phase II study - Kukiełka, Andrzej M.; Strnad, Vratislav; Stauffer, Paul; Dąbrowski, Tomasz; Hetnał, Marcin; Nahajowski, Damian; Walasek, Tomasz; Brandys, Piotr; Matys, Robert (Journal of Contemporary Brachytherapy, 2015)
Optimal treatment for patients with only local prostate cancer recurrence after external beam radiation therapy (EBRT) failure remains unclear. Possible curative treatments are radical prostatectomy, cryosurgery, and brachytherapy. Several single institution series proved that high-dose-rate brachytherapy (HDRBT) and pulsed-dose-rate brachytherapy (PDRBT) are reasonable options for this group of patients with acceptable levels of genitourinary and gastrointestinal toxicity. A standard dose prescription and scheme have not been established yet, and the literature presents a wide range of fractionation protocols. Furthermore, hyperthermia has shown the potential to enhance the efficacy of re-irradiation. Consequently, a prospective trial is urgently needed to attain clear structured prospective data regarding the efficacy of salvage brachytherapy with adjuvant hyperthermia for locally recurrent prostate cancer. The purpose of this report is to introduce a new prospective phase II trial that would meet this need. The primary aim of this prospective phase II study combining Iridium-192 brachytherapy with interstitial hyperthermia (IHT) is to analyze toxicity of the combined treatment; a secondary aim is to define the efficacy (bNED, DFS, OS) of salvage brachytherapy. The dose prescribed to PTV will be 30 Gy in 3 fractions for HDRBT, and 60 Gy in 2 fractions for PDRBT. During IHT, the prostate will be heated to the range of 40-47˚C for 60 minutes prior to brachytherapy dose delivery. The protocol plans for treatment of 77 patients.